Dietary specialization drives multiple independent losses and gains in the bitter taste gene repertoire of Laurasiatherian Mammals. Issue 1 (December 2016) - Liu, Zhijin; Liu, Guangjian; Hailer, Frank; Orozco-terWengel, Pablo; Tan, Xinxin; Tian, Jundong; Yan, Zhongze; Zhang, Baowei; Li, Ming
Abstract Background Bitter taste perception is essential for species with selective food intake, enabling them to avoid unpalatable or toxic items. Previous studies noted a marked variation in the number ofTAS2R genes among various vertebrate species, but the underlying causes are not well understood. Laurasiatherian mammals have highly diversified dietary niche, showing repeated evolution of specialized feeding preferences in multiple lineages and offering a unique chance to investigate how various feeding niches are associated with copy number variation for bitter taste receptor genes. Results Here we investigated the evolutionary trajectories ofTAS2R s and their implications on bitter taste perception in whole-genome assemblies of 41 Laurasiatherian species. The number of intactTAS2R s copies varied considerably, ranging from 0 to 52. As an extreme example of a narrow dietary niche, the Chinese pangolin possessed the lowest number of intactTAS2R s (n = 2) among studied terrestrial vertebrates. Marine mammals (cetacea and pinnipedia), which swallow prey whole, presented a reduced copy number ofTAS2R s (n = 0-5). In contrast, independent insectivorous lineages, such as the shrew and insectivorous bats possessed a higherTAS2R diversity (n = 52 andn = 20-32, respectively), exceeding that in herbivores (n = 9-22) and omnivores (n = 18-22). Conclusions Besides herbivores, insectivores in Laurasiatheria tend to have more functionalTAS2R s in comparison to carnivores and omnivores. Furthermore, animals swallowing food whole (cetacean, pinnipedia and pangolin) have lost most functionalTAS2R s. These findings provide the most comprehensive view of the bitter taste gene repertoire in Laurasiatherian mammals to date, casting new light on the relationship between losses and gains ofTAS2R s and dietary specialization in mammals.